1998
DOI: 10.1159/000030284
|View full text |Cite
|
Sign up to set email alerts
|

Malacoplakia or Prostate Cancer? Similarities and Differences

Abstract: Malacoplakia is a granulomatous inflammatory disorder clinically and ultrasonographically very similar to prostatic adenocarcinoma. Symptoms and physical findings are similar to prostatism and in half of the patients the differential diagnosis includes malignancy, mainly because of the presence of a hard nodule on digital rectal examination. Additionally, cases of malacoplakia can show hypoechoic nodes on transrectal ultrasound mimicking adenocarcinoma. We report a case of malacoplakia of the prostate with emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…In about half of the cases, the differential diagnosis includes malignancy, mainly because of the presence of a hard nodule on digital rectal examination and the hypoechoic areas seen on transrectal ultrasound imaging. [85][86][87][88][89] Malakoplakia is a poorly circumscribed lesion characterized by diffuse sheets of macrophages, mostly representing epithelioid histiocytes with granular eosinophilic cytoplasm (von Hansemann histiocytes), admixed with lymphocytes, plasma cells, and neutrophils (Figures 17d and e). They contain intracytoplasmic, spherical, sharply demarcated, and often concentrically laminated, basophilic inclusions, known as Michaelis-Gutmann bodies, which represent calcified bacterial debris (Figure 17e).…”
Section: Signet-ring Lymphocytesmentioning
confidence: 99%
See 1 more Smart Citation
“…In about half of the cases, the differential diagnosis includes malignancy, mainly because of the presence of a hard nodule on digital rectal examination and the hypoechoic areas seen on transrectal ultrasound imaging. [85][86][87][88][89] Malakoplakia is a poorly circumscribed lesion characterized by diffuse sheets of macrophages, mostly representing epithelioid histiocytes with granular eosinophilic cytoplasm (von Hansemann histiocytes), admixed with lymphocytes, plasma cells, and neutrophils (Figures 17d and e). They contain intracytoplasmic, spherical, sharply demarcated, and often concentrically laminated, basophilic inclusions, known as Michaelis-Gutmann bodies, which represent calcified bacterial debris (Figure 17e).…”
Section: Signet-ring Lymphocytesmentioning
confidence: 99%
“…Rare cases have been described in which malakoplakia and prostatic carcinoma have been simultaneously found in the prostate. [85][86][87][88][89] The finding of Michaelis-Gutmann bodies essentially excludes a diagnosis of high-grade prostatic carcinoma.…”
Section: Signet-ring Lymphocytesmentioning
confidence: 99%
“…The authors have reported such a patient with a raised PSA level of 38 μg/L [ 26]. TRUS can show hypoechoic areas mimicking prostate cancer [ 30] and prostate biopsies are thus essential to establish the diagnosis.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…Ultra-structural examination reveals inflammatory infiltrate rich in plasma cells and histiocytes. These histiocytes differ from tumour cells in their uniform, round or oval vesicular nuclei and finely vacuolated cytoplasm 6 . Within the cytoplasm of these histiocytes are found Michaelis-Guttmann bodies, which are characteristic to this condition.…”
Section: Discussionmentioning
confidence: 90%